1991
DOI: 10.2134/agronj1991.00021962008300040010x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Effects on Cotton Canopy Growth, Photosynthesis, and Respiration

Abstract: The ecological range of temperature conditions where cotton (Gossypium hirsutum L.) is commercially grown frequently exceeds the temperature range of available data. To predict growth, development, and responses of the primary physiological processes to those conditions, data at both lower and higher temperatures are needed. Cotton plants were grown in naturally lit, temperature‐ and CO2− controlled chambers. Plants grown at near‐optimum temperatures (30 and 35 °C day temperature) fixed twice as much CO2 at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
2

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 15 publications
9
66
2
Order By: Relevance
“…The model uses a reference maximum area of one leaf originally set at 150 cm 2 . However, leaf area of cotton can vary with node position at optimal conditions between 50 and 250 cm 2 (Reddy et al 1991(Reddy et al , 1992(Reddy et al , 1993(Reddy et al , 1995a(Reddy et al , b, 1997a. SIZELF for full sun conditions was estimated to be 320 cm 2 (Table 3) based on the much larger leaf size that cotton attained in this experiment; and SLAVAR value (Table 3) in the calibration was 230 cm 2 g -1 , higher than the default model value to accommodate for the relatively higher area-weight ratio of cotton leaves for this variety.…”
Section: Model Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The model uses a reference maximum area of one leaf originally set at 150 cm 2 . However, leaf area of cotton can vary with node position at optimal conditions between 50 and 250 cm 2 (Reddy et al 1991(Reddy et al , 1992(Reddy et al , 1993(Reddy et al , 1995a(Reddy et al , b, 1997a. SIZELF for full sun conditions was estimated to be 320 cm 2 (Table 3) based on the much larger leaf size that cotton attained in this experiment; and SLAVAR value (Table 3) in the calibration was 230 cm 2 g -1 , higher than the default model value to accommodate for the relatively higher area-weight ratio of cotton leaves for this variety.…”
Section: Model Calibrationmentioning
confidence: 99%
“…During the vegetative stage, photosynthesis would be less under shaded conditions than in full sun conditions and thus leaf area expansion can be sink-limited, thus limiting any effect of changes in SIZELF in predicting LAI. Other studies have shown that, in cotton, sink limitation occurs until the plant reaches about seven nodes and with leaf area of 320 cm 2 , after which the growth is totally source driven (Reddy et al 1991(Reddy et al , 1992(Reddy et al , 1993(Reddy et al , 1997a. This value (320 cm 2 ) was used as a parameter input in the model.…”
Section: Effects Of Leaf Size (Sizelf) On Laimentioning
confidence: 99%
“…Well watered plants were exposed to heat stress by increasing the ambient air temperature to 42 C (67% RH) during the light period and 25 C (40% RH) during the dark period. The optimal (control) temperature treatment (32 C) was selected as the upper limit of the thermal kinetic window for cotton (Burke et al 1988); the high temperature treatment of 42 C was selected to impose a sufficient heat load to adversely affect plant physiology and biochemistry (Reddy et al 1991;Bibi et al 2008).…”
Section: Temperature Treatmentsmentioning
confidence: 99%
“…These temperature increases can result in productivity losses across the current US cotton production belt (Reddy et al 2002, Pettigrew 2008. Although an optimum temperature range for cotton growth has been defined as 20 to 30°C by Reddy et al (1991), as 23.5 to 32°C by Burke et al (1988), and as 25.5°C for peak reproductive potential (Lokhande and Reddy 2014), there is as of yet no consensus optimal temperature range for cotton as the plant response to temperature varies among developmental stages and different plant parts (Burke and Wanjura 2009). In addition, cotton is grown successfully in climate where temperatures often exceed 40°C, such as India and Pakistan (Oosterhuis and Snider 2011).…”
Section: Introductionmentioning
confidence: 99%